2009
DOI: 10.1039/b821416f
|View full text |Cite
|
Sign up to set email alerts
|

Superparamagnetic graphene oxide–Fe3O4 nanoparticles hybrid for controlled targeted drug carriers

Abstract: A superparamagnetic graphene oxide -Fe 3 O 4 nanoparticles hybrid (GO-Fe 3 O 4 ) was prepared via a simple and effective chemical precipitation method. The amount of loading of Fe 3 O 4 on GO was estimated as 18.6 wt% by atomic absorption spectrometry. The hybrid was then loaded with doxorubicin hydrochloride (DXR) and the loading capacity was as high as 1.08 mg mg À1 . Both of the GO-Fe 3 O 4 hybrids before and after loading with DXR can be dispersed well in aqueous solution. They can congregate under acidic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
355
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 980 publications
(366 citation statements)
references
References 32 publications
8
355
1
2
Order By: Relevance
“…Previously, we have demonstrated that antibody functionalized SWCNTs possess expected adsorption capacity and release performance for Dox [34]. The loading and release performances of the FA-MWCNT@Fe nanocarriers were investigated and compared with a commonly used magnetic carrier, Fe 3 O 4 NPs [45][46][47].…”
Section: Drug Loading and Release Performance Of Fa-mwcnt@fementioning
confidence: 99%
“…Previously, we have demonstrated that antibody functionalized SWCNTs possess expected adsorption capacity and release performance for Dox [34]. The loading and release performances of the FA-MWCNT@Fe nanocarriers were investigated and compared with a commonly used magnetic carrier, Fe 3 O 4 NPs [45][46][47].…”
Section: Drug Loading and Release Performance Of Fa-mwcnt@fementioning
confidence: 99%
“…In addition, another challenge that impedes the practical application of Fe 3 O 4 is the production of iron-containing waste sludge, which introduces secondary pollution [7,8]. Hence, to overcome these disadvantages, significant efforts have been made to immobilize the Fe 3 O 4 particles onto various support materials, simultaneously preserving their unique magnetic property [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The functionalization of magnetic nanoparticles with carbon-based nanomaterials has recently attracted great interest as the resulting hybrid nanomaterials combine the properties of both building blocks. These hybrids can be applied in enzyme immobilization (Jiang et al, 2012;Gokhale et al, 2013) as well as in drug delivery (Yang et al, 2009;Mahmoudi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%